Application of Barbed Sutures in Laparoscopic Common Bile Duct Exploration: A Retrospective Analysis. Issue 5 (October 2018) - Liu, Xiangdong; Luo, De; Chen, Hong; Liu, Jiang; Peng, Fangyi; Fang, Cheng; Li, Bo; Su, Song
Abstract : Common bile duct (CBD) suturing is a difficult procedure in laparoscopic CBD exploration. We sought to develop a simpler CBD suture technique using running barbed sutures. We retrospectively compared 2 suture techniques for CBD closure after T-tube placement. The barbed group comprised of 46 patients who underwent CBD closure using running barbed sutures, whereas the standard group comprised of 39 patients who received interrupted sutures. Mean CBD suturing time (6.2±0.9 vs. 12.2±1.1 min; P <0.001), total operating time (79.7±9.4 vs. 90.8±12.4 min; P <0.001), and hospital stay (6.1±1.8 vs. 7.0±1.7 d; P =0.024) were significantly shorter and less patients experienced leakage after T-tube flushing ( P =0.041) with the barbed suture technique. There were 2 cases of postoperative bile leakage in the standard group, with no statistical significance. The running barbed suture technique is safe and effective for CBD closure, which can decrease operating time and risk of complications.